2′,7′-Dichlorodihydrofluorescein as a fluorescent probe for reactive oxygen species measurement: Forty years of application and controversy - Chen, Xiuping; Zhong, Zhangfeng; Xu, Zengtao; Chen, Lidian; Wang, Yitao (Free radical research, 2010)
Abstract Reactive oxygen species (ROS) are critically important chemical intermediates in biological studies, due to their multiple physiologically essential functions and their often pathologically deleterious effects. Consequently, it is vital that their presence in biological samples has to be quantifiable. However, their high activity, very short life span and extremely low concentrations make ROS measurement a scientifically challenging subject for researchers. One of the widespread methods for ROS detection, based on the oxidation of the non-fluorescent probe 2′,7′-dichlorodihydrofluorescein (DCFH2) to yield the highly fluorescent 2′,7′-dichlorofluorescein (DCF), was developed more than 40 years ago. However, from its initial application, argumentative questions have arisen regarding its action mechanisms, reaction principles and especially its specificity. Herein, the authors attempt to undertake a comprehensive review: to describe the basic characteristics of DCFH2; to discuss the present views of the mechanisms of its fluorescence formation; to summarize the fluorescence formation interferents; to outline its application in biological research; and to underline its advantages and disadvantages in ROS detection as well as for the methodological considerations that arise during analysis.